Effect of the USPSTF Grade D Recommendation against Screening for Prostate Cancer on Incident Prostate Cancer Diagnoses in the United States - Barocas, Daniel A; Mallin, Katherine; Graves, Amy J; Penson, David F; Palis, Bryan; Winchester, David P; Chang, Sam S (The Journal of urology, 2015)
In October 2011 the USPSTF (U.S. Preventive Services Task Force) issued a draft guideline discouraging prostate specific antigen based screening for prostate cancer (grade D recommendation). We evaluated the effect of the USPSTF guideline on the number and distribution of new prostate cancer diagnoses in the United States. We identified incident cancers diagnosed between January 2010 and December 2012 in NCDB (National Cancer Database). We performed an interrupted time series to evaluate the trend of new prostate cancers diagnosed each month before and after the draft guideline with colon cancer as a comparator. Incident monthly prostate cancer diagnoses decreased by -1,363 cases (12.2%, p<0.01) in the month after the USPSTF draft guideline and continued to decrease by 164 cases per month relative to baseline (-1.8%, p<0.01). In contrast monthly colon cancer diagnoses remained stable. Diagnoses of low, intermediate and high risk prostate cancers decreased significantly but new diagnoses of nonlocalized disease did not change. Subgroups of age, comorbidity, race, income and insurance showed comparable decreases in incident prostate cancer following the draft guideline. There was a 28% decrease in incident diagnoses of prostate cancer in the year after the USPSTF draft recommendation against prostate specific antigen screening. This study helps quantify the potential benefits (reduced harms of over diagnosis and overtreatment of low risk disease and disease found in elderly men) and potential harms (missed opportunities to diagnose important cancers in men who may benefit from treatment) of this guideline.